Active cutaneous anaphylaxis-inhibitory activity of Gamavuton-0 potassium (K-GVT-0) - Agung Endro Nugroho; Nunung Yuniarti; Enade Perdana Istyastono; Supardjan .; Lukman Hakim (Faculty of Pharmacy Universitas Gadjah Mada, Yogyakarta, Skip Utara, 55281, Indonesia, 2007)
Potassium Gamavuton-0 is a salt form of 1,5-bis(4’-hydroxy-3’-methoxyphenyl)-1,6-heptadiene-3,5 dione or gamavuton-0. Structure modification to a salt form is expected to result in a soluble compound which should have a better bioavailability. The purpose of this experimental study was to evaluate the inhibitory effects of potassium gamavuton-0 on active cutaneous anaphylaxis reaction induced by ovalbumin as an antigen.The study was performed using an active cutaneous anaphylaxis method followed by histopathological observation. The rats were subcutaneously sensitised by ovalbumin (OVA) and Al(OH)3 twice on the days of 0 and 7, and finally were challenged by ovalbumin on the day of 14 to induce active cutaneous anaphylaxis reaction. In order to determine the mast cells on the inflammation tissues, the specimens were stained with 0.1 % Alcian Blue (pH 0.3) and nuclear fast red. Under light microscopy, mast cells were identified as blue granules against a pale red backgound.The results showed that potassium gamavuton-0 at the doses of 20 and 40 mg/kg BW could inhibit the pigmentation area of vascular permeability on rats dorsal skin. It indicated that this compound has the inhibitory effect on active cutaneous anaphylaxis reaction with ED30 value of 28.26 mg/kg BW. Nevertheless, inhibitory effect of potassium gamavuton-0 was still lower than that of cromolyn sodium, a mast cell degranulation inhibitory drug. Histopathologically, the mechanism of inhibitory effect of potassium gamavuton-0 on active cutaneous anaphylaxis reaction is suggested through the inhibition on mast cell degranulation process responsible for releasing inflammation mediators such as histamine, serotonin.Key words: Gamavuton-0 potassium, anaphylaxis, mast cell, ovalbumin